Using soil bacteria to facilitate phytoremediation - Glick, Bernard R. (Biotechnology advances, 2010)
In the past twenty years or so, researchers have endeavored to utilize plants to facilitate the removal of both organic and inorganic contaminants from the environment, especially from soil. These phytoremediation approaches have come a long way in a short time. However, the majority of this work has been done under more controlled laboratory conditions and not in the field. As an adjunct to various phytoremediation strategies and as part of an effort to make this technology more efficacious, a number of scientists have begun to explore the possibility of using various soil bacteria together with plants. These bacteria include biodegradative bacteria, plant growth-promoting bacteria and bacteria that facilitate phytoremediation by other means. An overview of bacterially assisted phytoremediation is provided here for both organic and metallic contaminants, with the intent of providing some insight into how these bacteria aid phytoremediation so that future field studies might be facilitated.